Association of antioxidants use with the risk of dementia among community-dwelling adults in the United Kingdom biobank - Shang, Xianwen; Liu, Jiahao; Zhang, Xueli; Huang, Yu; Zhu, Zhuoting; Tang, Shulin; Wang, Wei; Ge, Zongyuan; Yu, Honghua; He, Mingguang (Frontiers in Nutrition, 2024)
Data regarding the association between antioxidant supplementation and incident dementia are limited.We included 494,632 adults (54.5% females) aged 40-71 years at baseline from the UK Biobank in the final analysis. Incident dementia was ascertained using hospital inpatient and death records up to January 2021.Over a median follow-up of 11.9 years, 7,128 new cases of all-cause dementia, 2,772 cases of Alzheimer's disease, and 1,397 cases of vascular dementia were recorded. The hazard ratio (95% CI) for incident dementia associated with zinc supplementation was 0.84 (0.74-0.96), and the association remained significant after adjusting for all confounders (0.84 (0.74-0.96)).In the full model, zinc supplementation was associated with a reduced risk of Alzheimer's disease (HR (95% CI): 0.71 (0.57-0.88)). There was no significant association between zinc supplementation and the risk of vascular dementia. No significant associations with incident dementia were observed for other antioxidant supplementation. The association between zinc supplementation and incident dementia was significant among individuals with (HR (95% CI): 0.34 (0.15-0.77)) and without cataract (0.87 (0.77-0.99)) but it was stronger among those with cataract (P-value for interaction=0.0271).